The Direct Costs of Microsurgical Resection of Vestibular Schwannomas. Issue 3 (March 2020) - Saliba, Joe; Mohammadzadeh, Amir; Tawfik, Kareem O.; Carriere, Junie S.; Schwartz, Marc S.; Nguyen, Quyen T.; Friedman, Rick A.
Abstract : Objective: To determine and itemize surgical costs associated with the translabyrinthine (TL), retrosigmoid (RS), and middle cranial fossa (MCF) approaches for microsurgical excision of vestibular schwannoma (VS). Study Design: Retrospective cost analysis study. Setting: Tertiary referral center. Patients: Thirty consecutive adult patients underwent microsurgical excision of VS by either TL, RS, or MCF approach (10 per approach). Interventions: Microsurgical excision of VS by one of the three major approaches. Medical and financial data were collected. Main Outcome Measures: Total operating room time (minutes), skin-to-skin time (minutes), operating room cost (US), and surgical supplies cost (US). Results: The MCF approach was associated with the shortest skin-to-skin time (230.3 min, p < 0.001). Mean overall nonsurgical room time was 94.7 minutes and not significantly different among approaches ( p = 0.55). Mean total surgical supplies cost was 5, 028 and was the highest for the RS (7, 116; p < 0.001) but not significantly different between TL and MCF. Mean operating room services charges were 68, 417 overall and were the lowest for the MCF group (53, 306; p = 0.01). Tumor size was not correlated with surgical supplies cost ( p = 0.74). The items associated with the highest average cost per case were the surgical aspirator (1, 062), drill burs (928), and titanium implants (575). There was redundancy in multiple surgical items such as drill burs, hemostatic agents, and sutures. Conclusion: This study is the first to provide a detailed itemization of the surgical expenses specific to VS resection. Elevated nonsurgical room time and supply redundancy provides the opportunity for decreasing surgical costs and waste.